Preclinical in vitro study of streptococcus mutans accumulation in three fixed retainer designs: Microbiological assay - Curado, Marcelo de Morais; Minervino, Bruno Lima; Leite, Cleiber de Oliveira; Salles, Loise Pedrosa; de Oliveira-Salles, Gustavo Henrique; Gandini, Luiz Gonzaga [UNESP]; Macedo, Sergio Bruzadelli (Japanese Society for Dental Materials and Devices, 2023)
The use of fixed retainers in the lower arch is frequent; however, its presence increases the accumulation of biofilm and dental calculus. The objective of this research was to evaluate, in vitro, the accumulation of Streptococcus mutans (S. mutans) in 3 designs of fixed retainers. Nine models were reproduced in heat-cured acrylic resin and divided into groups: straight retainer (SR), retainer with vertical strap (RVS), retainer with horizontal strap (RHS). The accumulation of S. mutans was assessed using the MTT assay (3-4,5-dimethyl-thiazol-2-yl-2,5-diphenyltetrazolium bromide) and then measured using an automated reader. The RHS group showed less biofilm accumulation compared to the other groups (p<0.05). The distance between the tooth surface and the retainer showed a strong negative correlation with biofilm accumulation (rs=−0.79, p=0.00037). The RHS showed significantly less accumulation of S. mutans due to the distance between the retainer and the tooth surface. This research provides relevant data for a future randomized clinical trial.
Keywords: Biofilm; Fixed retainer; Orthodontic retainer; Streptococcus mutans